Type-2 innate lymphoid cells control the development of atherosclerosis in mice - Stephen A. Newland (Nature Portfolio, 2017)
Type-2 innate lymphoid cells (ILC2) affect adipose tissue metabolism and function. Here the authors show that the ILC2 are present in para-aortic adipose tissue and represent a major source of IL-5 and IL-13 required for mounting atheroprotective immunity, which can be altered by high fat diet.